Estructura horizontal de especies comerciales del bosque de colina baja de la Comunidad Nativa Nuevo San Pablo, Quebrada Sinuya – distrito de Contamana – Loreto Perú. 2022 - Intakea Chamikag, Jamez Jesus Herly (2024)
The work was carried out in the low hill forest of the native community “Nuevo San Pablo, Quebrada Sinuya - District of Contamana -Loreto, Peru. In PC 1, a total of 459 trees, 18 commercial forest species and 12 botanical families were recorded, where the Fabaceae family contains the largest number of species (four species), followed by the families Malvaceae, Moraceae, Myristicaceae (two species), Bignoniaceae, Bombacaceae, Combretaceae, Euphorbiaceae, Lecythidaceae, Rubiaceae, Sapotaceae, Simaroubaceae (one species). In CP 02, a total of 886 trees, 18 commercial forest species and 11 botanical families were recorded, where the Fabaceae family contains the highest number of species (five species), followed by the families Myristicaceae, Malvaceae, Moraceae (two species), Euphorbiaceae, Simaroubaceae, Bombacaceae, Combretaceae, Bignoniaceae, Lecythidaceae, Rubiaceae (one species). IVI. PC 1. The yellow Catahua species is the most ecologically important species of the evaluated forest, which makes in total (157.826%). Also, it can be stated that two species report little participation with less than 5% of IVI, Copaiba (2.098%), and Cumala (2.003%) that together add up to 4.101% respectively. IVI. The species Catahua amarilla (58.052%), Aguanillo (48.037%) and Utucuro (33.651%), are the most important from the ecological point of view with a total (139.740%). Two species express low participation such as Azúcar Huayo (3.999%), and Shihuahuaco (2.609%) which together add up to.